Particle Swarm Optimization Based Sliding Mode Controller for Performance Improvement of Unified Power Quality Controllers Inverters - Mohammad Amin Heidari; Mehdi Nafar; Taher Niknam (مهندسی مخابرات جنوب)
In this paper particle swarm optimasation algorithm (PSO) based sliding mode controller(SMC) introduced to control invrters of Uniefied power quality Controllers(UPQC) to control and improve the power quality in microgrids through controlling the output power of the distributed generation source. In the proposed control scheme, the standard sliding mode controller (SMC) is used as a robust nonlinear controller, with the addition of the particle swarm optimization (PSO) algorithm - to determine the optimal parameters of the SMC controller. Using PSO added extra advantages like reducing chattering problems and increasing accuracy and tracking capability to the commonly knowns SMC benefits. To confirm the accuracy of the proposed controller's performance, computer simulation is performed under different system load conditions in the MATLAB/Simulink software environment. The obtained results show the effectiveness of the proposed control compared to the standard sliding mode controller in reducing harmonics, reducing voltage imbalance and improving other power quality indicators.